INTERAKSI SOSIAL SISWA TUNANETRA DALAM BELAJAR - DHYANA PUTRA ATMAJA, AGUS (Jurnal Pendidikan Khusus, 2015)
ABSTRACT Humans as social beings are required to perform relationship or social interaction for survival to meet the demands of life in groups. This is also true for students with visual impairment who are studying in inclusive school. This environment is very different from the special school environment, which students with visual impairment are interact only with the like. While in inclusive school, students are required to interact in an environment which is actually different from itself. Based on this, the researchers took the study focused on how the social interaction of students with visual impairment in learning in SMAN 10 Surabaya. Thus, this study aims to obtain data and information about the social interaction of students with visual impairments in learning during in the school environment. Source of data in this study is students with visual impairment, students alert (regular students), teacher, shadow teacher, library staff, and principal. The method used is descriptive qualitative method. Data collected through the interview process. Results of the study found that; (1) social interaction of students with visual impairments to alert students, teachers, library staff, and principals in learning in general can be expressed well. The level of student interaction with the visually impaired student and teacher alert occurs is higher than with principals and library staff; (2) The interaction of students with visual impairment with sighted students realized in the form of cooperation, positive competition, as well as the correspondence themselves; (3) Broadly speaking, students with visual impairment have the same academic achievement with sighted students in general, but has a non-academic achievements which tends to be better; (4) some problems in the social interaction with the teacher in the learning process, teaching materials which have not been modified, instructional media that do not support, facilities and infrastructure are lacking support, as well as the response of the majority of citizens who are less concerned school; (5) Efforts made them student with visual impairment, more active interaction in the form of question and answer with the teacher, through a peer tutor, trying to borrow a record company; and try to show the attitude of open interaction and behave well, thereby eliminating the negative stigma about private school community that is always dependent on other people.   Keywords:, social interaction,belajar